A Pilot Study of Enterade (VS001), an Oral Amino Acid Formulation, in Malnourished Bangladeshi Children with Environmental Enteric Dysfunction - Alam, Masud; Ferdous, Tahsin; Ara, Rifat; Siddique, Abdulla; Kabir, Mamun; Haque, Rashidul; Donowitz, Jeffrey R. (The American journal of tropical medicine and hygiene, 2025)
Environmental enteric dysfunction (EED) is a subacute syndrome characterized by increased intestinal inflammation and permeability that affects children in low-income countries. It is associated with growth and neurodevelopmental deficits, and there is currently no known treatment for EED. VS001 (AmiLyfe Bioscience, LLC, Norwood, MA) is a medical food (beverage) containing free amino acids that has been shown to decrease enteric inflammation and improve gut permeability in murine models. We conducted a double-blind, placebo-controlled pilot study to assess the acceptability and tolerability of VS001 in Bangladeshi children aged 1–2 years ( n = 10 per arm). We also examined the effects on EED biomarkers (lactulose–mannitol (LM) ratio, fecal lactoferrin, alpha-antitrypsin, myeloperoxidase, and neopterin). Participants received 8 oz. of VS001 or an identical vehicle without amino acids daily for 14 days. Tolerability and acceptability were measured using parental surveys and daily in-home adverse event monitoring. Subjects took an average of 118 minutes to complete the dose each day. Caregivers found the product convenient and easy to administer and either agreed or strongly agreed that they would give this product to their child again. None reported that the intervention negatively affected their child’s appetite. There were three mild adverse events deemed possibly related to the intervention, with two occurring in the active arm and one in the control arm. Children in the active arm exhibited a nonsignificant decrease in LM ratios (a marker of intestinal permeability) after treatment compared with the control arm (0.19–0.08 versus 0.19–0.17; P = 0.16). VS001 was acceptable to parents and reasonably well tolerated. Given the decrease in permeability observed in the active arm, a larger trial is warranted.